Analyzing the Effect of Brexit on the British Construction Industry Using Fuzzy Sets Theory - ElCheikh, Marwa; Cojocaru, Andreea; Theaker, Martin; AlSheikh, Dana (Frontiers in Built Environment, 2020)
Policymakers are continually facing new challenges that are exacerbated by the lack of dedicated analysis of how macroeconomic changes affect particular industries. One of the most current examples of this is the effect that Brexit will have on the British construction industry. This paper addresses the issue by deploying a new risk-based approach that utilizes the triangulation concept across risk impact, risk manageability, and the combination of those two factors. The novelty of this framework lies in the use of Fuzzy Theory to appraise the effect of a significant phenomenon when confronted with the absence of quantitative data. The research methodology adopts Fuzzy Sets Theory to assess the effect of Brexit upon the Human Resources, Currency, Trade, Funding, and Sovereignty areas of the industry to illustrate their vulnerability to time, cost, and reputation impacts. This novel approach overcomes biases by adopting Fuzzy set theory in assessing risks, and by focusing on the manageability of these risks in their external and internal environments, as opposed to the likelihood of risk occurrence. The research indicatively concluded that the areas most susceptible to Brexit are Human Resources and Currency, followed by Trade.